PRN and You - Abd Razak, Dzulkifli (1995)
There is no doubt that Malaysia is on course to realize its own vision, However as it progresses into the year 2020, there will be innumerable challenges that must be met. One such challenge is to avert any potential threat to human health that are posed by the rapid rate of industrialization. Going by what is taking place today the challenges could be formidable. The various incidents that took place last month should by now gives all of us a fair idea of what to expect in the year 2020 if we continue to be oblivious of our surrounding. The fact remains that there will be more and more chemicals being used in all walks of life, some continues to be released into the environment, others no doubt are poisonous. For example, waste fumes discharged into the atmosphere not only by industries but more commonly by motor vehicles will cause atmospheric pollution. Already there was some concern expressed over the increasing level of carbon monoxide gas in cities like Kuala Lumpur. Unfortunately this is not the only poisonous gas that are present in the air. Too much of tetraethyl lead and even carbon dioxide could result in a number of illeffects. The latter, in addition, will set up a 'greenhouse effect' causing the earth surface to warm up. What with the ozone layer diminishing the resultant impact cannot be overemphasised.